An Interdisciplinary Study Of Fiqh And Social Institutions: Islamic Family Law In Indonesia - Hartiningsih Hartiningsih (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2026)
Fikih constitutes a fundamental component of Islamic jurisprudence, regulating both religious obligations and the social interactions that shape Muslim communities. Rapid social transformation driven by globalization, technological advancement, and cultural change requires Islamic legal thought to remain faithful to the Sharīʿah while responding to contemporary realities. This article examines the contribution of interdisciplinary approaches to the study of fiqh, focusing on the development of Islamic family law in Indonesia. Using qualitative library research, it analyzes classical and contemporary works on Islamic jurisprudence alongside insights from sociology, anthropology, legal studies, and related disciplines. The study finds that interdisciplinary perspectives enrich juristic reasoning by situating Islamic legal norms within their broader social, cultural, and institutional contexts. This approach enhances the relevance of fiqh to contemporary issues, including family law reform, gender relations, digital transformation, and evolving patterns of social interaction, while remaining consistent with the objectives of Islamic law (maqāṣid al-sharīʿah). It further demonstrates that interdisciplinary inquiry expands the analytical framework of Islamic legal studies and supports the development of Islamic family law that is more contextual, adaptive, and responsive to the needs of contemporary Indonesian society.